2021
DOI: 10.3390/biomedicines9060648
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycoumarin Scopoletin Inhibits Bone Loss through Enhancing Induction of Bone Turnover Markers in a Mouse Model of Type 2 Diabetes

Abstract: Diabetes induces bone deterioration, which leads to increased risk of fracture, osteopenia, and osteoporosis. Thus, diabetes-associated bone fragility has been recognized as a diabetic complication. However, the pathophysiological effects of hyperglycemia on bone turnover remain unclear. Literature evidence demonstrates that anti-diabetic medications increase the risk of fractures in individuals with type 2 diabetes. Scopoletin is a naturally occurring hydroxycoumarin potentially exhibiting anti-inflammatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…6 In addition, its antioxidant activities have been indicated in multiple studies. 7,8 Scopoletin could inhibit the proliferation as well as motility of cervical cancer cells and promote the apoptosis of prostate cancer cells by regulating the PI3K/AKT signaling pathway. 8 Scopoletin also inhibits the proliferation of immature dendritic cells (DC) and has anti-angiogenic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In addition, its antioxidant activities have been indicated in multiple studies. 7,8 Scopoletin could inhibit the proliferation as well as motility of cervical cancer cells and promote the apoptosis of prostate cancer cells by regulating the PI3K/AKT signaling pathway. 8 Scopoletin also inhibits the proliferation of immature dendritic cells (DC) and has anti-angiogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Scopoletin could inhibit the proliferation as well as motility of cervical cancer cells and promote the apoptosis of prostate cancer cells by regulating the PI3K/AKT signaling pathway. 8 Scopoletin also inhibits the proliferation of immature dendritic cells (DC) and has anti-angiogenic effects. In addition, scopoletin inhibits dendritic cell activation and the pathogenesis of autoimmune encephalomyelitis via nuclear factor kappa B (NF-κB) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This study investigated whether fsCH ameliorated the expression of osteogenic proteins of BMP-2, BSPII, and osteopontin during 21 day-osteoblastic differentiation. The cellular BMP-2 expression was enhanced significantly at the early–mid stage of differentiation [ 40 ]. The treatment of pre-osteoblastic cells with isoflavone, GPH, PH, and GP in osteogenic media did not influence the induction of BMP-2 ( Figure 6 D).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have revealed that scopoletin (1-20 µM) improves osteoclast formation in diabetes through RANKL and enhances osteoclast formation in diabetes by inducing BMP-2 and Runx2. Oral administration of 10 mg/kg scopoletin promotes the formation of bone trabeculae and collagen fibers in the femoral epiphysis and metaphysis of type 2 diabetes mice (Lee et al, 2021). Aldose reductase (AR) is a crucial ratelimiting enzyme that contributes to cataract induction among patients with diabetes.…”
Section: Antidiabetic Activitymentioning
confidence: 99%